2005
DOI: 10.1080/02791072.2005.10399820
|View full text |Cite
|
Sign up to set email alerts
|

Antiquity of Coca-Leaf Chewing in the South Central Andes: A 3,000 Year Archaeological Record of Coca-Leaf Chewing from Northern Chile

Abstract: Carbon-14 (14C) dating from mummies of the Alto Ramirez culture confirms that coca leaf chewing was an incipient practice among members of a population that peopled the valleys and coastal areas of Northern Chile by 3,000 years before the present (yr.B.P.). Out of eleven bodies from the burial site of Pisagua-7 (PSG-7, S 19 degrees 35', W 70 degrees 13') that were analyzed, two samples tested positive. Mummy 725-A C2 (dated 3,090 to 2,850 two sigma calibrated 14C years before the present) was shown to have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 6 publications
0
18
0
5
Order By: Relevance
“…However, such studies have been particularly enlightening in archaeological contexts (Wilson, 2005). Chemical analysis of hair from mummies from the area around Arica in Northern Chile has shown intake of cocaine, most likely from coca leaves (Cartmell et al, 1991a,b;Springfield et al, 1993;Rivera et al, 2005), while a similar study from the same general geographic area suggested the consumption of harmine (Ogalde et al, 2009; but see Trout, 2008), an alkaloid and monoaminooxidase inhibitor (MAO-I) present in the vine Banisteriopsis sp. (Malpighiaceae).…”
Section: Introductionmentioning
confidence: 96%
“…However, such studies have been particularly enlightening in archaeological contexts (Wilson, 2005). Chemical analysis of hair from mummies from the area around Arica in Northern Chile has shown intake of cocaine, most likely from coca leaves (Cartmell et al, 1991a,b;Springfield et al, 1993;Rivera et al, 2005), while a similar study from the same general geographic area suggested the consumption of harmine (Ogalde et al, 2009; but see Trout, 2008), an alkaloid and monoaminooxidase inhibitor (MAO-I) present in the vine Banisteriopsis sp. (Malpighiaceae).…”
Section: Introductionmentioning
confidence: 96%
“…The coca leaf was chewed or used to make tea to combat fatigue and altitude sickness. Traces of coca have been found in mummified human cadavers dating back 3000 years [115] and probably millennia before this. The French naturalist Joseph de Jussieu Local anaesthetic agents have become one of the mainstays of modern surgery.…”
Section: Facit Ad Maximos Dolores -Useful For Extreme Painmentioning
confidence: 99%
“…is also the approximate date of the supposed origin of the use of tea in China. It is likely that coca leaf chewing began in the Andes at the same time since traces of coca have been found in mummies dating 3000 years back (5). The cocaine content of coca leaf is under 1% but after 1859, when cocaine was first isolated from coca leaf by Albert Niemann, cocaine was available legally in concentrations that were nearly 100% pure.…”
Section: Drug Use: a Behaviour As Old As Humankind?mentioning
confidence: 99%